RISK ASSESSMENT IN FINANCIAL AUDIT - Elena RUSE (SEA: Practical Application of Science, 2018)
Audit risk is the risk of expressing an inappropriate audit opinion with reference to financial statements that are materially misstated. Risks exist but the audit objective is to mitigate the audit risk to an acceptable level. The process of auditing the annual financial statements involves a series of stages until the opinion is expressed and during the audit, the materiality threshold and the audit risk are analyzed together. There is a link between the professional judgment used by the auditor during the course of the mission, the auditor's perception of the financial information needs of the users of the financial statements, and the general significance threshold for the overall financial statements. Particular attention will be paid to managing risks by management within the organization. Each organization has a responsibility in managing risks up to the acceptable level (risk tolerance). The auditor will apply risk assessment procedures and the evaluation of the results is based on the assessment of the probability of their materialization and the impact of the risk.